Взаємозв’язки законів педагогічної творчості зі специфікою формування інноваційної культури майбутнього фахівця - Штефан, Людмила Володимирівна (НТУ "ХПІ", 2015)
На основі аналізу законів педагогічної творчості було визначено їх взаємозв’язки із особливостями формування інноваційної культури майбутніх фахівців. У центрі уваги були закони: педагогічної розвивальної взаємодії, фасилітаційного режиму педагогічного впливу, взаємообумовленості розвитку суб’єктів педагогічного процесу, неперервної творчої реалізації та самореалізації особистості.

On the basis of analysis of laws of pedagogical creation their intercommunication was certain with the features of forming of innovative culture of future specialists. In a center attention there were laws: pedagogical developing cooperation, falisitation regime of pedagogical influence, interconditionality of development of subjects of pedagogical process, continuous creative realization and self-realization of personality.
Intercommunications of laws of pedagogical creation with the specific of forming of innovative culture of future specialist
Keywords: педагогічна розвивальна взаємодія; закони; творча реалізація; фасилітація; самореалізація особистості; cooperation; innovative culture; developmen; creation; falisitation